Prevalencia y Carga Parasitaria Invernal en Heces de Canis latrans (coyote) del Ârea Natural Protegida Médanos de Samalayuca México - Petters-Cabrera, José Gaspar (2019)
The knowledge of the parasites present in wild animals of especial area can give us an overview of the general state and conservation of these as well as the degree of alteration of the sitewhere they are. The main of this research was to determine the winter prevalence and parasitic load in coyote feces of the Médanos de Samalayuca Protected Natural Area (PNA), Chihuahua, Mexico. The collection of feces was carried out in two areas of the PNA, area 1 with human intervention and area 2 less disturbed, 70 feces were collected throughout the winter 2018/19, they were analyzed by coproparasitoscopic techniques of Centrifuge-Flotation in NaCl, Formalin and egg count per gram in Mc Master chambers, to determine the mean parasitic intensity and the prevalence of parasites. The results were the following: the total prevalence was 70%, being the Toxocara genus the most prevalent and Entamoeba the least prevalent, the highest prevalence of parasites was recorded in area 2 being 93% and for area 1 of 53%. Parasitic genus Strongyloides 800hpg, Toxocara 535hpg, Physaloptera 200hpg, Taenia 200hpg, Ancylostoma 175hpg and Toxascaris140hpg found no differences or trends between both areas.